First results from the IllustrisTNG simulations: the stellar mass content of groups and clusters of galaxies - Pillepich, Annalisa; Springel, Volker; Pakmor, Rüdiger; Weinberger, Rainer (Arxiv, 2018)
The IllustrisTNG project is a new suite of cosmological magneto-hydrodynamical simulations of galaxy formation performed with the Arepo code and updated models for feedback physics. Here we introduce the first two simulations of the series, TNG100 and TNG300, and quantify the stellar mass content of about 4000 massive galaxy groups and clusters ($10^{13} ≤ M_{\rm 200c}/M_{\rm sun} ≤ 10^{15}$) at recent times